Contested understandings of nature in Nicaragua´s South-east - Tittor, Anne (Revista Científica Foz, 2022)
Departing from theoretical and empirical insights from Political Ecology, this case study analyses the claims of different social groups about Nature in south-eastern Nicaragua. The analysis draws on expert interviews conducted during field research in 2014, 2015, and 2016 and contextualizes the findings within the history of Nicaragua. Environmentalists refer to the area as habitat of endangered species, whereas peasants perceive it as “agricultural frontier”. Politicians see a high potential of this sparsely populated territory for the extraction of resources or the construction of an Interoceanic canal. For most indigenous and afro-descendent leaders, however, this is the land of the ancestors. From their point of view, the attitudes of the Nicaraguan government and the peasants are a continuation of centuries of colonialism and racism.